An Ethnobotanical Study of Indigenous Leafy Vegetables Among Local Communities in Bintulu, Sarawak, Malaysia - SAUPI, NOORASMAH; SAIDIN, AINUL ASYIRA; ZAKARIA@YA, MUTA HARAH; SARBINI, SHAHRUL RAZID; YUSLI, NURUL AISYAH (Borneo Journal of Resource Science and Technology, 2020)
The consumption of indigenous leafy vegetables (ILV) is a common practice among local people in Bintulu. It serves as an important food resource for local communities in rural areas. However, these traditional practices were declining in urban areas and among younger generations. Therefore, the study aimed to record the ILV consumed by the local people, and mode of consumption of the ILV. A field survey was carried out with two phases; phase one was the distribution of structured questionnaires and the second phase was the interview session with 20 respondents from each of the three native markets located in Bintulu Division; Bintulu, Tatau, and Sebauh market. The study has identified 20 species of ILV from 18 different families: Agavaceae, Anacardiaceae, Athyriaceae, Blechnaceae, Brassicaceae, Compositae, Euphorbiaceae, Flacourtiaceae, Gnetaceae, Leguminosae, Limnocharitaceae, Menispermaceae, Myrtaceae, Olacaceae, Ophioglossaceae, Piperaceae, Smilacaceae and Verbenaceae. Identified ILV were consumed in many ways by the natives. The plant parts used also differ from one species to another and had different taste. A further study should be carried out to analyse the plant nutritional values and agronomy factors for commercialization of the potential ILV. Keywords: Bintulu, consumption method, ethnobotany, ethnobotanical study, indigenous leafy vegetables